2012
DOI: 10.1371/journal.pone.0031591
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Treatment and Correlation with Risk of Hospitalization among Commercially Insured HIV Patients in the United States

Abstract: PurposeA lower daily pill burden may improve adherence to antiretroviral treatment (ART) and clinical outcomes in patients with human immunodeficiency virus (HIV). This study assessed differences in adherence using the number of pills taken per day, and evaluated how adherence correlated with hospitalization.MethodologyCommercially insured patients in the LifeLink database with an HIV diagnosis (International Classification of Diseases, 9th Revision, Clinical Modification code 042.xx) between 6/1/2006 and 12/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 26 publications
6
124
0
Order By: Relevance
“…As also observed in other chronic diseases, such as HIV infection, 68,69 regimen complexity seems to be another barrier to CML medication adherence as described by the recent cross-sectional study in the US and EU. 43 Difficulties related to treatment following BCR-ABL inhibitor therapy has been shown to be a significant factor affecting adherence, with dietary and dosing restrictions being associated with greater difficulty.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 61%
“…As also observed in other chronic diseases, such as HIV infection, 68,69 regimen complexity seems to be another barrier to CML medication adherence as described by the recent cross-sectional study in the US and EU. 43 Difficulties related to treatment following BCR-ABL inhibitor therapy has been shown to be a significant factor affecting adherence, with dietary and dosing restrictions being associated with greater difficulty.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 61%
“…1,21 STRs that reduce pill burden to as little as 1 pill taken once daily have been associated with improved adherence, reduced hospitalizations, and improved viral suppression. [22][23][24][25][26] In our study, patients who received STRs were about 1.3 times more likely to be adherent (i.e., MPR ≥ 90%) than patients receiving more than 1 (N = 3,528) antiretroviral product. Several studies showing an association with STR use and improved adherence involved the STR efavirenz/emtricitabline/tenofovir disoproxil fumarate (Atripla), [23][24][25][26] which is a recommended regimen for treatment-naïve patients per the HHS 2011 Guidelines.…”
Section: ■■ Discussionmentioning
confidence: 94%
“…1 One study concluded that patients on this fixed-dose STR reported a lower percentage of hospitalizations and emergency room visits. 24 Over 30% of all HIV-infected patients on antiretroviral therapy in the United States already use the STR efavirenz/emtricitabine/tenofovir disoproxil fumarate, and pharmaceutical sales experts predict that it will have the highest antiretroviral sales by 2013. 27 Since the end of the time frame in which we evaluated ART regimens (i.e., 2010), 2 additional STRs have been approved by the U.S. Food and Drug Administration: emtricitabine/rilpivirine/tenofovir disoproxil fumarate (Complera) in 2011 and elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil fumarate (Stribild) in 2012.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the group of patients with schizophrenia, a discriminant function analysis was performed with "Absolute Treatment Adherence" as a categorical dependent variable and the scores on the PANSS and PSQI as predictor variables. Furthermore, two multiple regression analyses [36] were conducted with one analysis containing "Degree of Treatment Adherence" as the dependent variable and the score on the BDI-II, as well as the score on the PSQI, as independent variables for the group of patients with depression. In the second analysis, "Degree of Treatment Adherence" was used as the dependent variable, and the score on the PANSS, as well as the score on the PSQI, were used as independent variables for the group of patients with schizophrenia.…”
Section: Design and Statisticsmentioning
confidence: 99%